RETRACTED: Sugarcane Derived Polyphenol Feed Additive Supplemented to the Wheat Diet Improved Broiler Performance (Nepalese Veterinary Journal, 2023)
This article was retracted on 4th March 2025. It was published without permission from the authorities at the authors' institution.